2002
DOI: 10.1070/rc2002v071n05abeh000718
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature superconductors based on complex layered copper oxyfluorides

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…A detailed discussion of the utilisation of xenon difluoride for the fluorination of complex oxides and analysis of the processes accompanying fluorination may be found in a recent review. 67 Oxofluorides Sr 2 MnGaO 57x F 1+x were synthesised starting from completely oxidised Sr 2 MnGaO 5.5 at 500 ± 600 8C using an anion exchange reaction, which gives rise to a decrease in the formal oxidation state of manganese. 56,68 Sr2MnGaO5.5 + 1 x 2 XeF2…”
Section: Complex Oxofluorides Sr 2 Mngao 57x F 1+xmentioning
confidence: 99%
“…A detailed discussion of the utilisation of xenon difluoride for the fluorination of complex oxides and analysis of the processes accompanying fluorination may be found in a recent review. 67 Oxofluorides Sr 2 MnGaO 57x F 1+x were synthesised starting from completely oxidised Sr 2 MnGaO 5.5 at 500 ± 600 8C using an anion exchange reaction, which gives rise to a decrease in the formal oxidation state of manganese. 56,68 Sr2MnGaO5.5 + 1 x 2 XeF2…”
Section: Complex Oxofluorides Sr 2 Mngao 57x F 1+xmentioning
confidence: 99%
“…In other words, effects of F − doping on the structure, electronic chemistry and the transfer rate of photogenerated electrons to the photocatalyst surface are beneficial to an increase of photocatalytic activities [10]. It is well known that the studies of synthetic, structural, and electronic aspects of F − for O 2− substitutions have also been particularly important [11,12]. For example, the synthesis of superconductor Sr 2 CuOF 2+ı was reported [13].…”
Section: Introductionmentioning
confidence: 97%
“…Insulating layered compounds containing 3d 9 Cu 2+ ions have been widely investigated because of their unique structural, optical, electrical, and magnetic properties. In particular, since the discovery of the high- T c superconducting cuprates by Bednorz and Müller, there has been considerable progress, as well as controversy, about the physics and chemistry of not only superconducting copper oxides but also copper oxyfluorides. , Moreover, considerable interest has recently been shown in the solid-state chemistry of fluorides that contain the 4d 9 Ag 2+ ions, including prediction of superconducting phases, charge-transfer character, and two-dimensional ferromagnetism. , A landmark question to understand these materials is how their physical properties follow from their electronic structure and to what extent simplified descriptions in the form of model Hamiltonians describe their basic physical properties in the normal state. In this sense, it has long been argued that, besides the canonical 3d x 2 – y 2 copper orbital, the 3d 3 z 2 – r 2 one plays an important role in the onset for the existence of superconductivity or orbital order, and therefore, different authors have suggested that the transition temperature, T c , is directly related to the magnitude of the d x 2 – y 2 –d 3 z 2 – r 2 splitting, Δ. Optical absorption measurements and resonant inelastic X-ray scattering (RIXS) spectra carried out on some copper oxides and fluorides ,− have provided detailed insight into the d–d transitions and the actual value of Δ of these materials.…”
mentioning
confidence: 99%
“…1−9 In particular, since the discovery of the high-T c superconducting cuprates by Bednorz and Muller, 1 there has been considerable progress, as well as controversy, about the physics and chemistry of not only superconducting copper oxides 2−10 but also copper oxyfluorides. 11,12 Moreover, considerable interest has recently been shown in the solid-state chemistry of fluorides that contain the 4d 9 Ag 2+ ions, including prediction of superconducting phases, charge-transfer character, and two-dimensional ferromagnetism. 13,14 A landmark question to understand these materials is how their physical properties follow from their electronic structure and to what extent simplified descriptions in the form of model Hamiltonians describe their basic physical properties in the normal state.…”
mentioning
confidence: 99%